PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Melinasari, Susi; Iskandar, Lina (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This community service activity was held in collaboration with the LPPM Sahid Bogor Islamic Institute and the Purwabakti Women's Group, Gunung Sari Village. In general, the activities carried out smoothly without any problems. Housewives have an important position as family financial regulators. The background to the implementation of the activity is due to the level of understanding of the target partners on the importance of planning and how to manage family finances which is still relatively low. Target partners also do not understand the importance of investing to increase family income. The purpose of this counseling is to provide understanding and knowledge about the importance of financial planning and how to carry out good financial management in the family environment.